THE EFFECT OF VOCABULARY MASTERY ON STUDENTS WRITING SKILLS IN DESCRIPTIVE TEXT AT SMP NEGERI 4 BAUBAU - Maneba, Sanaria; Wahyuni B, Asti; Nurmayanri AS, Nurmayanri AS (English Education Department, 2023)
Problem statement of this research was whether there is a significant effect of vocabulary mastery on students writing skills in descriptive text of eight grade students at SMP Negeri 4 Baubau. Objective of this research was to find out whether there is a significant effect of vocabulary mastery on students' writing skills in descriptive text of eight grade at SMP Negeri 4 Baubau. Data collection in this study was carried out using a research instrument in the form of a test to students to determine the correlation between students' vocabulary mastery on students' writing skills in descriptive text. This research is a quantitative research. The subjects of this study were 55 grade eight students of SMP Negeri 4 Baubau. Data were analyzed using Statistical Product and Service Solution (SPSS) version 21.0. Based on the results of research and data analysis, it was concluded that there was a correlation between vocabulary mastery on students' writing skills in descriptive text of eight grade at SMP Negeri 4 Baubau. This conclusion is based on the results of statistical analysis which found a significance level of 0.939 with an r table value of 0.266. The rxy value is greater than the r table value (0.939> 0.266) and the significance value is less than (0.5) or in other words the Null hypothesis (HO) is rejected and the alternative hypothesis (H1) is accepted.